Participatory assessment and the construction of professional identity in folk and popular music programs in Finnish and Australian music universities. (November 2015) - Partti, Heidi; Westerlund, Heidi; Lebler, Don
Assessment in music is of considerable importance in the context of higher music education, with major projects focusing on assessment principles and practices in a number of locations, including the European community and Australia. This instrumental case study explores assessment practices in two higher music education contexts, namely within folk music education in Finland and popular music education in Australia. While each of these two instances have significant individual characteristics, they share a focus on understanding assessment as learning and the development of a professional identity through the active participation of the student community in the assessment processes. Drawing on current theories of communities of practice, the narratives of the leaders describing the practices in each context are analysed to draw attention to the intended learning value derived through the participatory assessment practices.